Effects of lactation and nursery diets supplemented with a feed flavor and increasing tryptophan:lysine ratio in DDGS based diets with or without a DDGS withdrawal strategy in growing-finishing pigs - Spinler, Mikayla Sue (Kansas State University, 2023)
The first chapter of this thesis analyzed the effects of a feed flavor in the sow lactation and nursery diets on sow feed intake and lactation performance and subsequent weaned pig nursery performance. A total of 105 sows were used across four batch farrowing groups. Dietary treatments included a standard corn-soybean-based lactation diet or the control diet with the addition of a feed flavor included at 0.05% of the diet. Overall, sows fed the flavor treatment had a tendency for greater ADFI compared with control sows. In the nursery portion of the study, 360 weaned pigs were used in a 2 × 2 factorial with main effects of previous sow feed flavoring treatment (control vs flavor) and nursery diets formulated with or without a feed flavor on growth performance in a 38-d trial. Offspring from sows fed the flavor diet were heavier at weaning which was maintained throughout the study. Overall, progeny from sows fed a diet containing a feed flavor had greater ADG, ADFI, and final BW during the trial, but the presence of a feed flavor in the nursery did not improve overall nursery performance. The second chapter compared increasing tryptophan:lysine ratios in DDGS-based diets with or without a DDGS withdrawal strategy on growth performance and iodine value of growing-finishing pigs. A total of 6,240 finishing pigs, divided into 2 groups, were used in a 119 or 120 d study. Pigs were allotted to 1 of 7 treatments consisting of a control corn-soybean meal-based diet formulated to a 19% standardized ileal digestibility Trp:Lys ratio, 4 diets with 30% DDGS fed in all four phases, and formulated to provide SID Trp:Lys ratios of 16, 19, 22, or 25%, and 2 DDGS withdrawal strategy diets with 19% SID Trp:Lys with 30% DDGS in phase 1 through 3 and then 0% DDGS in phase 4 with either a 19 or 25% Trp:Lys ratios. Increasing the SID Trp:Lys ratio in diets with 30% DDGS resulted in a linear increase in ADG, ADFI, G:F, and BW but did not influence carcass fat IV. Removing DDGS from the diet in the last period reduced carcass fat IV and increased growth rate during the withdrawal period compared to pigs fed 30% DDGS throughout, indicating value in a withdrawal strategy.
Keywords: Carcass characteristics; Grow-finish pigs; Tryptophan; Feed flavor; Sow lactation; Nursery pig